CIRSE Standards of Practice on Varicocele Embolisation - Ierardi, Anna Maria; Biondetti, Pierpaolo; Tsetis, Dimitrios; Del Giudice, Costantino; Uberoi, Raman (Cardiovascular and interventional radiology, 2023)
Background Percutaneous embolisation is an effective, minimally invasive means of treating a variety of benign and malignant lesions and has been successfully used to treat varicoceles since the late 1970s, with refined and expanded techniques and tools currently offering excellent outcomes for varicocele embolisation. Purpose This document will presume that the indication for treatment is clear and approved by the multidisciplinary team (MDT) and will define the standards required for the performance of each modality, as well as their advantages and limitations. CIRSE Standards of Practice documents are not intended to impose a standard of clinical patient care, but recommend a reasonable approach to, and best practices for, the performance of percutaneous varicocele embolisation. Methods The writing group was established by the CIRSE Standards of Practice Committee and consisted of five clinicians with internationally recognised expertise in embolisation of male varicoceles. The writing group reviewed the existing literature on varicocele embolisation, performing a pragmatic evidence search using PubMed to search for publications in English and relating to human subjects published from 2006 to 2021. The final recommendations were formulated through consensus. Conclusion Embolisation has an established role in the successful management of male varicoceles. This Standards of Practice document provides up-to-date recommendations for the safe performance of varicocele embolisation.